2016 10th International Conference on Software, Knowledge, Information Management &Amp; Applications (SKIMA) 2016
DOI: 10.1109/skima.2016.7916232
|View full text |Cite
|
Sign up to set email alerts
|

Route scheduling for HSSP using adaptive genetic algorithm with constructive scheduling technique

Abstract: Shortest path finding has been a challenging task in most of the complex multipath scenarios. The complexity rises with the introduction of constraints to the scenarios. Healthcare service to the patient is one of the real world problems where travelling path has significant impact on the service time. The purpose of this research is to develop new approach to solve multiple travelling salesman problem (MTSP) for healthcare staff members offering healthcare services at patients homes travelling in different ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The first step creates possible demand service scenarios while the second stage estimates the optimal number of staff members offering the service. In our previous works, the experimental results (Sinthamrongruk, 2016), (Sinthamrongruk and Dahal, 2017) indicated that hybrid approach based on Genetic Algorithm (GA) provided the optimal service route.…”
Section: Introductionmentioning
confidence: 99%
“…The first step creates possible demand service scenarios while the second stage estimates the optimal number of staff members offering the service. In our previous works, the experimental results (Sinthamrongruk, 2016), (Sinthamrongruk and Dahal, 2017) indicated that hybrid approach based on Genetic Algorithm (GA) provided the optimal service route.…”
Section: Introductionmentioning
confidence: 99%